The Emory‐Sage‐SGC TREAT‐AD Center: Tool and probe development for emerging targets in Alzheimer's Disease. (20th December 2022) - Leal, Karina; Axtman, Alison D.; Betarbet, Ranjita; Brennan, Paul E; Carter, Gregory W; Frye, Stephen V.; Fu, Haian; Greenwood, Anna K; Longo, Frank M.; Pearce, Kenneth H.; Edwards, Aled M; Levey, Allan I.; et al.
Abstract: Background: Alzheimer's disease is the most common form of dementia and there is currently no effective therapy for either treatment or prevention. With repeated failure in DRUG DEVELOPMENT across industry and demonstrated heterogeneity in biological and genetic components of the disease, there is a need to evaluate a broad range of therapeutic hypotheses for target prioritization. The Emory‐Sage‐SGC TREAT‐AD Center (https://treatad.org) is generating and openly distributing validated experimental tools necessary to test target predictions generated through sequence‐based characterization of human disease state. We believe that these tools and reagents, including chemical and biological probes that target the multifaceted dysregulation in the brains of AD patients will advance the discovery of potential drug targets for AD. Method: The Emory‐Sage‐SGC TREAT‐AD Center uses integrated computational approaches to identify target predictions from a set of prioritized therapeutic hypotheses. Emerging AD targets derived from systems biology studies within the Accelerating Medicines Partnership in AD (AMP‐AD) consortium and additional NIA‐supported AD consortia were mapped to 15 biological domains (BDs) and prioritized based on an unbiased bioinformatic assessment across multiple lines of evidence for overall AD‐risk. Targets are then evaluated to identify a set of experimental reagents necessary for hypothesis testing, termed a "target enablement package (TEP). Result: Within these 15 biological domains, we prioritized more than 30 targets for target enabling package (TEP) development. TEPs include expression constructs, knockout cell lines, assays, antibody validation, and crystal structures. All reagents are developed to meet established quality criteria. For a subset of tractable targets (MSN, SYK, SFRP1, SDC4 and CAPN2), chemical probe development is underway to provide tools to test these therapeutic hypotheses in cellular and animal systems. TREAT‐AD investigators place all data, knowledge, reagents, and tools into the open domain with no intellectual property claims. Conclusion: The open drug discovery approach of TREAT‐AD is aimed to de‐risk potential AD therapeutics to catalyze robust and independent evaluation of a diverse portfolio of promising yet untested AD therapeutic hypotheses. All data, protocols, reagent sets, and chemical tools will be made widely available on the AD Knowledge Portal. For more information see www.treatad.org.